Pembelajaran E learning dan Perubahan Perilaku Belajar Pada Masa Pandemi Covid 19 (Universitas Negeri Semarang, 2022)
Covid-19 pandemic leads to government policy to enact social distancing and physical distancing to prevent Covid-19 transmission. Some of the actions taken by the government are closing schools by replacing face-to-face learning with e-learning. This learning change is felt very hard both by educators, students, and parents. For Educators the demand for creativity in delivering material is one of the reasons for the difficulty of online learning. In addition to causing physical and mental pressure, it also makes it more difficult for schools to determine scores or benchmarks for students' assessment. The learning process during the Covid-19 pandemic can be done through learning management system based applications such as google classroom, google meet, zoom meeting, and whatsApp. The study aims to decide variations in the use of LMS-based e-learning platforms, show factors that influence the inhibition of e-learning, and find the effect of variations in the use of e-learning platforms on learner learning behavior. This type of research is qualitative with survey data collection techniques. The results showed that the e-learning platform based on learning management system that is often used by 78.1% of students is Google classroom. However, in practice there are several inhibiting factors such as 61% of students saying geographical location, and 41.9% limitations of infrastructure facilities or equipment such as the lack of internet quota. In addition, the implementation of e-learning results in changes in learning behavior of students who are enthusiastic about participating in the learning